Introduction to mechatronics and measurement systems - Alciatore, David G. (McGraw-Hill, 2007)
Introduction to Mechatronics and Measurement Systems provides comprehensive and accessible coverage of the evolving field of mechatronics for mechanical, electrical and aerospace engineering majors. The authors present a concise review of electrical circuits, solid-state devices, digital circuits, and motors- all of which are fundamental to understanding mechatronic systems.